Understanding psychology students’ perspective on video psychotherapy and their intention to offer it after graduation: a mixed-methods study - Meier, Jennifer Virginie; Noel, Josephine Alexandra; Kaspar, Kai (Frontiers in Psychology, 2023)
Introduction Video psychotherapy (VPT) demonstrated strong clinical efficacy in the past, with patients and psychotherapists expressing satisfaction with its outcomes. Despite this, VPT only gained full recognition from the German healthcare system during the COVID-19 pandemic. As society increasingly relies on new media, it seems likely that VPT will become even more relevant. Previous studies surveyed practicing psychotherapists and patients about advantages and disadvantages of VPT. In contrast, our approach targets a younger generation, specifically psychology students intending to become licensed practitioners after graduation. Methods Our mixed-methods study was conducted in an online survey format and had two main objectives. Firstly, we investigated which person-related variables are associated with psychology students’ behavioral intention to offer VPT after graduation, using a multiple regression analysis. Secondly, we explored psychology students’ perception of advantages and disadvantages of VPT and identified their desired learning opportunities regarding VPT in their study program, using qualitative content analysis. Results A sample of 255 psychology students participated. The multiple regression model explains 73% of inter-individual variance in the intention to offer VPT, with attitudes toward VPT showing the strongest relationship with intention to offer VPT. Expected usefulness, satisfaction with video conferencing, and subjective norm also showed significant relations. The students provided 2,314 statements about advantages, disadvantages, and desired learning opportunities, which we coded by means of three category systems. In terms of advantages, the most frequently mentioned categories were low inhibition threshold, flexibility in terms of location, and no need to travel. For disadvantages, the predominant categories included lack of closeness between patient and psychotherapist, lack of nonverbal cues, and problems with technology or internet connection. Regarding desired learning opportunities, training for technical skills, practical application through role-playing and self-experience, and general information about VPT were the most mentioned categories. In addition, we identified numerous other aspects related to these topics, reflecting a differentiated and balanced assessment of VPT. Discussion We discuss the theoretical and practical implications of our findings for training the next generation of psychotherapists and outline a specific five-step plan for integrating VPT into study programs.